Lemongrass (Cymbopogon Citratus) Essential Oil Inhibits Candida Albicans Growth in Vitro - Yoga Mulia Pratama; Bryan Pandu Permana (Biomedika, 2020)
Candidiasis is an important nosocomial infection with high morbidity value, high mortality rate, and expensive clinical cost. However, public access to well-developed treatment is not acquired. Current medicines mostly used like -azol drugs had been showing the resistant effects because of the long period use of the same medicines. Alternative medicines like herb medicine are discussed to reduce multi-resist infections, such as lemongrass Cymbopogon citratus essential oil. This study aims to know the effect of lemongrass essential oil on the growth of Candida albicans in vitro. Laboratory experimental (in vitro) was conducted in this research. Candida albicans strains were being used as the objects, which were picked by random sampling. Candida albicans were divided into 12 groups of treatment, the group I was treated with ethanol 96% as the negative control, group II with fluconazole 25μg as the positive control, and group III-XII with Cymbopogon citratus essential oil with 10%, 20% to 100% concentrated. The diameter of inhibition zones was measured after 2x24 hours incubation. The data was analyzed by post-hoc Mann Whitney test with SPSS 18.0 (p<0.05 considered as significant). Cymbopogon citratus essential oil showed antifungal activity to the Candida albicans began in the 10% to 100% concentration (p<0.05). Inhibition zones with the 50% to 100% concentration had similar results to the positive control (p>0.05). The Cymbopogon citratus essential oil has an antifungi effect toward Candida albicans in vitro significantly by the negative control.